1972
DOI: 10.1017/s0021859600025752
|View full text |Cite
|
Sign up to set email alerts
|

Changes associated with pregnancy and lactation in some extra–reproductive organs of the ewe

Abstract: The food intake, the apparent digestibilities of dry matter, and of nitrogen were measured in housed Blackface ewes during late pregnancy, lactation, and after the lambs were weaned. The ewes were slaughtered serially together with non-breeding controls, and the liver, ruminal mucosa, intestines, CNS and carcass were weighed. In association with differing reproductive status marked changes occurred in the content of dry matter and protein in the alimentary organs, but not in the CNS, and the mean weight of DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
45
1
2

Year Published

1980
1980
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 21 publications
(24 reference statements)
3
45
1
2
Order By: Relevance
“…These results are consistent with those from other studies that have reported that increased DM intake is associated with gut hypertrophy (Fell et al 1972;Fell and Weekes 1975). Significant increases in GIT mass with increased level of feed intake have been reported, and these have been associated with increases in some or all of the components of the stomach complex and the small intestine in lambs (Burrin et al 1990) and steers (Johnson et al 1987).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…These results are consistent with those from other studies that have reported that increased DM intake is associated with gut hypertrophy (Fell et al 1972;Fell and Weekes 1975). Significant increases in GIT mass with increased level of feed intake have been reported, and these have been associated with increases in some or all of the components of the stomach complex and the small intestine in lambs (Burrin et al 1990) and steers (Johnson et al 1987).…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with those from the current study, and we can surmise that the relative weights of GIT components, even though they were not calculated in the present study, responded to level of feed intake similarly to absolute weights. Dietary composition also had a significant effect on weights of GIT components, with steers fed diets O and A having consistently heavier GIT component weights compared to those fed diet S. This increase may be partly due to the significantly higher DM intake of steers fed diets O and A compared to those fed diet S. This could have resulted in increases in visceral organ mass as has been reported elsewhere (Fell et al 1972;Fell and Weekes 1975). Additionally, steers fed diet S had the highest NDF intakes compared to those fed diets O and A, and this could have resulted in a lower GIT diet digestibility (Glenn et al 1989;Prigge et al 1990) and, presumably, reduced feed intake due to gut fill.…”
Section: Discussionsupporting
confidence: 61%
“…†The following assumptions were made, or taken from Fell et al (1972), Frandson (1986), Agricultural and Food Research Council (1993) and Klasing & Calvert (1999): lymph represents 10% total blood volume, packed cell volume of blood is 0·33, blood volume is 8% body weight, immune cells weigh 2 × 10 −10 g and contain 18% protein, half-life of IgA and lymphocytes is 7 d, half-life of mucosal mast cells is 1·5 d, efficiency for protein synthesis is 0·85, plasma contains 60-75 g protein/l, abomasum volume is 1·4 litres, abomasal folds and glands increase the abomasal surface by a factor of 10, the abomasum weighs 250 g of which 20% is mucosa.…”
Section: Metabolisable Protein Requirement For Expression Of Immunitymentioning
confidence: 99%
“…Non-specific regulation refers to gross changes in absorptive function that are associated with long-term or homeorhetic changes in physiological state, such as pregnancy or lactation, and generally involves synchronous upregulation of all nutrient transporters ). For example, lactation and pregnancy are normally associated with increased intestinal transport capacity that is associated with increases in mucosal growth and in the absorptive surface area (Fell et al 1972;Hammond and Diamond 1994).…”
Section: Regulation Of Glucose Absorptionmentioning
confidence: 99%